2021
DOI: 10.1016/j.molmet.2021.101275
|View full text |Cite
|
Sign up to set email alerts
|

Neddylation inhibition ameliorates steatosis in NAFLD by boosting hepatic fatty acid oxidation via the DEPTOR-mTOR axis

Abstract: Objective Neddylation is a druggable and reversible ubiquitin-like post-translational modification upregulated in many diseases, including liver fibrosis, hepatocellular carcinoma, and more recently, non-alcoholic fatty liver disease (NAFLD). Herein, we propose to address the effects of neddylation inhibition and the underlying mechanisms in pre-clinical models of NAFLD. Methods Hepatic neddylation measured by immunohistochemical analysis and NEDD8 serum levels measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Based on these premises, we described the importance of neddylation, a reversible PTM, for immune activation in COVID-19 patients and the potential efficacy of MLN4924, the pharmacological inhibitor of neddylation. We have recently described that neddylated proteins appear in the serum of patients with liver pathology, which is associated with disease progression [ 30 ]. High levels of proteins in the blood could be a sign of chronic infection or inflammation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these premises, we described the importance of neddylation, a reversible PTM, for immune activation in COVID-19 patients and the potential efficacy of MLN4924, the pharmacological inhibitor of neddylation. We have recently described that neddylated proteins appear in the serum of patients with liver pathology, which is associated with disease progression [ 30 ]. High levels of proteins in the blood could be a sign of chronic infection or inflammation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for protein isolation and western blotting was described in Serrano-Maciá et al, 2021 [ 30 ]. Protein gels were transferred into nitrocellulose blotting membranes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that hepatic neddylation was induced in clinical and preclinical non-alcoholic fatty liver disease (NAFLD), suggested by increased NEDD8 expression levels. 90 Notably, specific knockdown of NEDD8 in hepatocytes could be achieved by injecting AAV-DIO-shNedd8 into Alfp-Cre transgenic mice, which efficiently reduced neddylation levels and lipid accumulation in the livers of mice induced by a high-fat diet with choline deficiency, thereby inhibiting the development of NAFLD to NASH. 90 …”
Section: The Application Of Aav-mediated Gene Delivery System In Live...mentioning
confidence: 99%
“… 90 Notably, specific knockdown of NEDD8 in hepatocytes could be achieved by injecting AAV-DIO-shNedd8 into Alfp-Cre transgenic mice, which efficiently reduced neddylation levels and lipid accumulation in the livers of mice induced by a high-fat diet with choline deficiency, thereby inhibiting the development of NAFLD to NASH. 90 …”
Section: The Application Of Aav-mediated Gene Delivery System In Live...mentioning
confidence: 99%